Clinical Presentation & Dyslipidemia in Post-Menopausal Women with Acute Myocardial Infarction (The Planet, 2024)
Introduction: While most CHD risk factors are similar between men and women, they can often vary in strength and association and change throughout their lifetime. This is especially evident for lipids, with low high-density lipoprotein cholesterol (HDL-C) cholesterol and hypertriglyceridemia being stronger predictors of CHD in women than in men. Aim of the study: This study aimed to analyze the clinical presentation and dyslipidemia in post-menopausal women with acute myocardial infarction. Methods and materials: This cross-sectional descriptive study was carried out at the Department of Medicine and Department of Cardiology, Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh, from January 2019 to July 2019. A total of 105 postmenopausal women with acute myocardial infarction (AMI) were selected purposively. Data entry and descriptive analysis were done using SPSS (Statistical Package for Social Science) for Windows version 20.0. Output of data and graphical representation was done using Microsoft Office chart and Microsoft Word. Result: On ECG, arrhythmia was seen in 34.28% of subjects. Ischemia was observed in 30.47% subjects. Old MI (15.23%) was also evident in ECG. A majority (36.19%) of the subjects had
Keywords: Post-menopausal; Dyslipidemia; Acute myocardial infarction; Ischemia